Influence of cleansers and a phytotherapic against Candida albicans on the properties of denture liners (Revista da Faculdade de Odontologia - UPF, 2014)
Objectives: The aims of this study were to evaluate the antimicrobial activity and effect of denture cleansers and the phytotherapic Plantago australis Lam. on mechanical properties of two resilient denture liners. Materials and method: Samples of acrylic and silicone based materials were submitted to biofilm formation using 24-well polystyrene cell tissue culture plates to form C. albicans biofilm for 1, 7 and 14 days. The specimens were subjected to the following treatments: distilled water, 0.5% sodium hypochlorite, sodium perborate and Plantago australis Lam. Counts of Candida were calculated and the results expressed in colony forming units (CFU)/mm2. The following analyses were performed: sorption and solubility, surface roughness and scanning electron microscopy (SEM). Results: Three-way ANOVA showed a statistically significant difference between materials (p